Description of a specific bronchial provocation test for the diagnosis of occupational asthma due to platinum salts / Descrizione di un test di provocazione bronchiale specifica per la diagnosi di asma professionale da sali di platino - Porro, S.; Cerri, S.; Bernabeo, et al., F. (La Medicina del Lavoro, 2012)
SummaryBackground: Occupational exposure to platinum salts may cause the onset of skin and respiratory disorders with an IgE-mediated allergic mechanism. The diagnosis of occupational asthma due to platinum salts was, in a small number of cases, achieved also via  occupational specific bronchial provocation tests (sBPT), which until now were conducted by pouring platinum salt dusts from one tray to another or by direct aerosoling of hexachloroplatinate solutions into the patient’s airways. Methods: Here we describe an original occupational sBPT based on atomization of solutions of ammonium hexachloroplatinate, at increasing concentrations, in a 5 m3 challenge room: the starting solution is a 1:100 dilution of the preset threshold of the patient’s skin reactivity to the substance. In the absence of a bronchoconstrictive response, the following concentration is atomized (each time 10 times higher than the previous one), until the maximum concentration, 10-2 M, is reached. The patient is not in the challenge room during atomization of the solutions, but enters when this operation has been completed and remains there for 15 minutes, unless he/she shows signs of respiratory trouble before that time. After each exposure, the patient is clinically monitored, with respiratory function tests at preset times, until at least 8 hours after the end of the exposure. Results and Conclusions: The test allowed identifying a respiratory hypersensitivity specifically to platinum as cause of asthma in two precious metal workers, with the onset of immediate bronchospasm in one patient and biphasic bronchospasm in the other. Compared to the sBPT by pouring a mixture of platinum salt dusts from one tray to another, the method we designed offers a better standardization of bronchial stimulation and, compared to direct aerosoling of hexachloroplatinate into the patient’s airways, it has the advantage of reproducing the respiratory risk conditions occurring in the workplace and offers better safety guarantees for the patient, since it reduces the risk of onset of serious asthmatic or even systemic responses in subjects highly hypersensitive to this metal.Riassunto«Descrizione di un test di provocazione bronchiale specifica per la diagnosi di asma professionale da sali di platino». Introduzione: L’esposizione lavorativa a sali di platino può causare l’insorgenza di patologia cutanea e respiratoria con meccanismo allergico IgE mediato. La diagnosi di asma professionale da platino in non molti casi si è avvalsa anche dell’effettuazione di test di provocazione bronchiale specifica (TPBs) professionale, finora condotti con la metodica del travaso di miscele di polveri di sali di platino o con quella dell’aerosolizzazione diretta di soluzioni di esacloroplatinato nelle vie aeree del paziente. Metodi: Descriviamo una metodica originale di TPBs professionale basata sulla nebulizzazione di soluzioni di ammonio esacloroplatinato, a concentrazioni crescenti, in cabina di esposizione di 5 m3: la concentrazione di partenza è una diluizione 1:100 della soglia predeterminata in base alla reattività cutanea del paziente alla sostanza; in assenza di risposta broncocostrittiva si procede con l’erogazione in atmosfera della concentrazione successiva (ogni volta 10 volte più elevata rispetto alla precedente), fino a terminare con la concentrazione massima  di 10-2 M. Il paziente non è presente in cabina durante la nebulizzazione delle soluzioni; vi entra al suo termine e vi staziona per 15 minuti a meno di una più precoce insorgenza di disturbi respiratori. Dopo ogni esposizione egli viene monitorato clinicamente e con prove di funzionalità respiratoria a tempi prefissati, fino ad almeno 8 ore dal termine dell’esposizione. Risultati e conclusioni: Il test ha consentito di individuare come causa dell’asma di 2 lavoratori di metalli preziosi una condizione d’ipersensibiltà respiratoria specifica a platino, con insorgenza di broncospasmo  immediata in uno e difasica nell’altro. Rispetto al TPBs condotto con il travaso di miscela di polveri di sali di platino il metodo da noi messo a punto è caratterizzato da una miglior standardizzazione della stimolazione bronchiale; rispetto all’aerosolizzazione diretta di esacloroplatinato nelle vie aeree del paziente ha il vantaggio di riprodurre le modalità del rischio respiratorio che si verificano sul lavoro e di offrire maggiori garanzie di sicurezza per il paziente, in quanto riduce il rischio d’insorgenza di gravi risposte asmatiche od anche sistemiche in soggetti marcatamente ipersensibili al metallo.